Interaction of C1q With Pentraxin 3 and IgM Revisited: Mutational Studies With Recombinant C1q Variants - Bally, Isabelle; Inforzato, Antonio; Dalonneau, Fabien; Stravalaci, Matteo; Bottazzi, Barbara; Gaboriaud, Christine; Thielens, Nicole M. (Frontiers in Immunology, 2019)
Pentraxins and complement defense collagens are soluble recognition proteins able to sense pathogens and altered-self elements and to trigger immune responses including complement activation. PTX3 has been shown to interact with the globular recognition domains (gC1q) of the C1q protein of the classical complement pathway, and to modulate complement activity. Previous mutagenesis studies had been performed on the individual gC1q domain of each of the three C1q chains and the present study aimed at revisiting the C1q-PTX3 interaction using full-length recombinant C1q. Four mutations targeting exposed amino acid residues in the gC1q domain of each of the C1q chains (LysA200Asp-LysA201Asp, ArgB108Asp-ArgB109Glu, TyrB175Leu and LysC170Glu) were introduced in recombinant C1q and the PTX3 interaction properties of the mutants were analyzed using surface plasmon resonance (SPR). The impact of these mutations on C1q interaction with IgM and on PTX3-and IgM-mediated complement activation was also investigated. The LysA200Asp-LysA201Asp and LysC170Glu mutants retained a partial ability to interact with PTX3 and IgM, but triggered efficient complement activation. In contrast, the ArgB108Asp-ArgB109Glu mutation abolished C1q binding to PTX3 and IgM, and significantly decreased complement activation. The TyrB175Leu mutant exhibited decreased PTX3- and IgM-dependent complement activation. Our studies confirm a key contribution of Arg residues of the B chain located on the side of the gC1q heterotrimer in PTX3- and IgM-C1q interaction, and a lower participation of a Lys residue located at the apex of gC1q.